INNOVATION IN THE CONSTRUCTION INDUSTRY - Martino Tangkar; David Arditi (Civil Engineering Dimension, 2000)
In this paper%2C existing innovation models are reviewed. The influence of technology and market-driven schools of thought on the creation and diffusion of innovation is examined. Incremental vs. radical models and autonomous vs. systemic models are considered in the context of the construction industry. The concept of %93technology adoption life cycle%94 is investigated to understand better the acceptance of new technology by key parties. A new model of innovation is proposed. In this model%2C the transformation process of invention into adoption flows through a cyclical mechanism encompassing six phases%3A 1%29 need%2C 2%29 creation%2C 3%29 invention%2C 4%29 innovation%2C 5%29 diffusion%2C and 6%29 adoption. This model clearly shows the interaction of the three most influential domains%3A users%2C changes%2C and the environment. The model also takes into consideration the influence of technology and market-driven forces on the creation and diffusion of innovation. As a consequence of their particular function in the construction activity%2C construction management firms should perform as catalysts in the generation and diffusion of technological advances in the Abstract in Bahasa Indonesia : Innovation%2C+invention%2C+innovation+models%2C+technology+adoption+life+cycle%2C+construction+management.+